Operationalizing Trust: Building the Online Trust Student Survey (OTSS) - Hai-Jew, Shalin (My University, 2010)
This research study explores the creation of a survey instrument to explore the role “trust” plays in highly interactive, instructor-led online college courses offered by WashingtonOnline Virtual Campus (WAOL-VC). After an extensive review of the literature, a 47-item Online Trust Student Survey (OTSS) was created to operationalize the construct of “trust” based on online learner perception. This instrument explored “trust” relationships between learner and instructor; learner and fellow learners; learners and curriculum; learners and oversight organization; and learners and courseware technology. From this instrument, principal component variables were extracted for analysis. With a .922 score of the Kaiser-Meyer-Olkin Measure of Sampling Adequacy, the OTSS instrument offered strong ground for confidence coupled and with absence of multi-collinearity. In the first run, 630 current freshmen and sophomore students were surveyed. Post-survey online interviews were subsequently administered to investigate perceptions of learners in “low-trust” and “high-trust” categories. Additional interviews were conducted with distance learning (DL) or e-Learning instructors and administrators. The rigorous use of this instrument served as a test for its wide-ranging respondent accessibility and efficacy. The paper overviews the development of these instruments and offers insight into potential areas of further research.
Keywords: Online Trust Student Survey; OTSS; Trust in online learning; Distrust/mistrust; Trust propensity; Telepresence; Peer-to-peer relations; Online survey; Perennial Survey; Post-survey online interviews